Covid-19 Treatment in Hadith Perspective - Andi Mujahidil Ilman; Andi Muhammad Ali Amiruddin (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2022)
Corona Virus Disease 2019 is a virus that first appeared in the Wuhan area, China. The virus appeared in mid-2019 and then reportedly entered Indonesia at the end of 2019. This virus attacks the respiratory organs so that it has a convulsive effect on people who are infected and is contagious with various transmission media. One of the methods used to suppress the spread of the virus is by injecting the Covid-19 vaccine. Islam as a religion that is elastic in the times and places has been explained based on the substance of the Qur’an and Hadith. Rasulullah SAW. has explained the importance of treatment when contracting a disease. In this paper, we will explain the views of the Prophet’s Hadith regarding the order for treatment with the existence of a covid-19 vaccine.